"Hay for the Hobby Horses": Reflections on the Air War in the South Atlantic 1982. Issue 1 (2nd January 2022) - Mason, R. A.
Abstract : Editorial Note: This article was originally published in the RUSI Journal in 1982 (Volume 127, Issue 4). While the article has been reformatted and a typographical error has been removed, the text is an otherwise authentic reproduction of the original version. Several images that were included in the original version have not been reproduced.◼